2007
DOI: 10.5194/acp-7-97-2007
|View full text |Cite
|
Sign up to set email alerts
|

Validation of SCIAMACHY top-of-atmosphere reflectance for aerosol remote sensing using MERIS L1 data

Abstract: Abstract. Aerosol remote sensing is very much dependent on the accurate knowledge of the top-of-atmosphere (TOA) reflectance measured by a particular instrument. The status of the calibration of such an instrument is reflected in the quality of the aerosol retrieval. Current data of the SCIA-MACHY (SCanning Imaging Absorption spectroMeter for Atmospheric CHartographY) instrument (operated with the data processor version 5 and earlier) give too small values of the TOA reflectance, compared e.g. to data from MER… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…These values are also in agreement with our results, which are based on a much larger dataset. We note that whereas [7] followed an approach identical to this letter, including in the linear fit different scenes, von Hoyningen-Huene et al [8] based their results on a particular cloud-free case over the sea (i.e., a dark scene). Furthermore, SCIAMACHY cloud-top retrievals using the O -A band at 760 nm (FRESCO method [16]) confirm a correction factor of about 1.20 in the NIR (N. Fournier and R. van der A., KNMI, personal communication).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These values are also in agreement with our results, which are based on a much larger dataset. We note that whereas [7] followed an approach identical to this letter, including in the linear fit different scenes, von Hoyningen-Huene et al [8] based their results on a particular cloud-free case over the sea (i.e., a dark scene). Furthermore, SCIAMACHY cloud-top retrievals using the O -A band at 760 nm (FRESCO method [16]) confirm a correction factor of about 1.20 in the NIR (N. Fournier and R. van der A., KNMI, personal communication).…”
Section: Discussionmentioning
confidence: 96%
“…Using several clear pixels over the Baltic Sea, von Hoyningen-Huene et al [8] compared the calibration of SCIAMACHY and MERIS. They found nm nm nm , and nm…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the numbers are different for different surfaces combined with the large spread found for 865 nm indicates that calibration issues are very likely not the cause of the differences. Also, the radiometric calibrations of SCIAMACHY and MERIS have been compared extensively in the past [ Acarreta and Stammes , ; von Hoyningen‐Huene et al , ; Kokhanovsky et al , ] and the instruments are expected to agree within a few percent.…”
Section: Ler Database Intercomparisonsmentioning
confidence: 99%
“…In the first year after the launch of SCIAMACHY [ Bovensmann et al , 1999], a number of studies showed indications of severe shortcomings in its radiometric calibration [see, e.g., Skupin et al , 2003; Acarreta and Stammes , 2003]. The shortcomings in the reflectance calibration were confirmed later on for the UV by comparison with radiative transfer models [ van Soest et al , 2005; Tilstra et al , 2005] and for visible and near‐infrared wavelength ranges by comparison with the satellite instruments Medium‐Resolution Imaging Spectrometer (MERIS) and GOME [ Acarreta and Stammes , 2005; von Hoyningen‐Huene et al , 2006; Tilstra and Stammes , 2006]. Most notable was the 15–25% underestimation of the reflectance by SCIAMACHY.…”
Section: Introductionmentioning
confidence: 99%